Numerical simulation and mechanism analysis of gas explosion suppression by ultrasonic water mist. Issue 23 (2nd December 2019) - Wang, Fahui; Chen, Wei; Wen, Xiaoping; Zhao, Weilong; Liu, Zhichao
ABSTRACT: Aimed at reducing the occurrence of gas explosion accidents, this work explored the mechanism and effect of ultrasonic water mist suppression on gas explosion. On the basis of EDC combustion model, the experimental and numerical results are compared and verified. It shows that the flame temperature, flame propagation velocity, and maximum explosion pressure are obviously decreased when ultrasonic water mist is added into the pipeline, and the descending proportion increases with the increment of the water mist concentration, which implies the ultrasonic water mist can effectively restrain gas explosion. The maximum error of the flame propagation time and the flame propagation velocity is within 10%, the maximum error of the explosion pressure is about 10%, which means the model is reliable and the numerical simulation results are in good agreement with the experimental results. Furthermore, the reaction rate of the generated water and the evaporation rate of water mist were studied, the mechanism and effect of the ultrasonic water mist on gas explosion suppression were further discussed.